A phase 2 study of the PARP inhibitor veliparib plus temozolomide in patients with heavily pretreated metastatic colorectal cancer. Issue 11 (26th March 2018) - Pishvaian, Michael J.; Slack, Rebecca S.; Jiang, Wei; He, A. Ruth; Hwang, Jimmy J.; Hankin, Amy; Dorsch‐Vogel, Karen; Kukadiya, Divyesh; Weiner, Louis M.; Marshall, John L.; Brody, Jonathan R.
Abstract : BACKGROUND: Poly(adenosine diphosphate ribose) polymerase (PARP) inhibitors such as veliparib are potent sensitizing agents and have been safely combined with DNA‐damaging agents such as temozolomide. The sensitizing effects of PARP inhibitors are magnified when cells harbor DNA repair defects. METHODS: A single‐arm, open‐label, phase 2 study was performed to investigate the disease control rate (DCR) after 2 cycles of veliparib plus temozolomide in patients with metastatic colorectal cancer (mCRC) refractory to all standard therapies. Fifty patients received temozolomide (150 mg/m 2 /d) on days 1 to 5 and veliparib (40 mg twice daily) on days 1 to 7 of each 28‐day cycle. Another 5 patients with mismatch repair–deficient (dMMR) tumors were also enrolled. Twenty additional patients were then treated with temozolomide at 200 mg/m 2 /d. Archived tumor specimens were used for immunohistochemistry to assess mismatch repair, phosphatase and tensin homolog deleted on chromosome 10 (PTEN), and O(6)‐methylguanine‐DNA methyltransferase (MGMT) protein expression levels. RESULTS: The combination was well tolerated, although some patients required dose reductions for myelosuppression. The primary endpoint was successfully met with a DCR of 24% and 2 confirmed partial responses. The median progression‐free survival was 1.8 months, and the median overall survival was 6.6 months. PTEN protein expression and MGMT protein expression were not predictors of DCR. There was also a suggestion of worse outcomes for patients with dMMR tumors. CONCLUSIONS: In this heavily pretreated mCRC population, a combination of veliparib and temozolomide was well tolerated with temozolomide doses up to 200 mg/m 2 /d, and it was clinically active. PARP inhibitor–based therapy merits further exploration in patients with mCRC. Cancer 2018;124:2337‐46 . © 2018 American Cancer Society . Abstract : This study presents the results of a phase 2 trial of veliparib plus temozolomide for patients with metastatic colon cancer. The combination has been found to be well tolerated, with disease control achieved in 24% of patients (with 2 confirmed partial responses). There is a suggestion of worse outcomes for patients with a mismatch repair deficiency, and there is no correlation between phosphatase and tensin homolog deleted on chromosome 10 or O(6)‐methylguanine‐DNA methyltransferase protein expression and disease control.